Handheld XRF for Art and Archaeology - Mass, Jennifer L.; Shugar, Aaron N. (Book collections on Project MUSE., 2012)
"Over the last decade the technique of X-ray fluorescence has evolved from dependence on laboratory-based standalone units to field use of portable and lightweight handheld devices. These portable instruments have given researchers in art conservation and archaeology the opportunity to study a broad range of materials with greater accessibility and flexibility than ever before. In addition, the low relative cost of handheld XRF has led many museums, academic institutions, and cultural centres to invest in the devices for routine materials analysis purposes. Although these instruments often greatly simplify data collection, proper selection of analysis conditions and interpretation of the data still require an understanding of the principles of x-ray spectroscopy. These instruments are often marketed and used as 'point and shoot' solutions; however, their inexpert use can easily generate deceptive or erroneous results"--Page 4 of cover.